Using mobile augmented reality games in education - Videnovik, Maja; Vold, Tone; Kiønig, Linda; Madevska Bogdanova, Ana; Trajkovik, Vladimir (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
Incorporating mobile augmented reality games into formal education has the potential to enhance student engagement and motivation, as well as to promote learning outcomes in a more interactive and enjoyable manner. However, this requires careful consideration of pedagogical principles to ensure that those mobile games align with educational objectives and standards. The proposed methodological approach aims to provide a framework for teachers and educators to effectively incorporate mobile augmented reality games into their teaching while also providing a means of evaluating the effectiveness of the approach in enhancing student learning outcomes and developing their skills and competences.
Keywords: mobile augmented reality games, situated learning, outdoor learning, microlearning, spaced repetition